Evaluating the Impact of Ayurvedic Interventions on Renal Health in Chronic Kidney Disease: A Case Study Analysis (Journal of Food and Dietetics Research, 2025)
Chronic kidney disease (CKD) is a global health issue that has attracted attention owing to its increasing mortality rate. The disease is classified into five stages according to the glomerular filtration rate (GFR). It is difficult to diagnose CKD in its early stages (stages I and II) because the GFR might remain normal. The exact cause of CKD remains unclear; however, lifestyle changes and dietary factors are often associated with its development. A multidisciplinary treatment approach is considered the most effective for managing CKD. Panchakarma encompasses detoxification and rejuve nation techniques that aim to balance the doshas, enhance kidney function, and promote overall wellness. Despite the availability of advanced technologies and treatments, early detection remains elusive in developing and middle-income countries. This case report focuses on a 69-year-old male patient with CKD for 7 months and hypertension for 20 years who received Ayurvedic treatment at Jeena Sikho Lifecare Limited Hospital, Derabassi. CKD is prevalent in the elderly population owing to age-related physiological changes, increased comorbidities, and cumulative exposure to risk factors such as hypertension and diabetes. The treatment regimen administered to him integrated personalized Ayurvedic principles and Panchakarma therapies, resulting in a significant improvement in his symptoms, kidney function, and overall quality of life. After six days of therapy, the patient demonstrated an improved glomerular filtration rate (GFR) and reported considerable relief from pain and other related symptoms. These results highlight Ayurveda’s potential as an affordable treatment modality that can complement or even replace conventional therapies, particularly in individuals with limited financial resources seeking advanced healthcare options. Despite these promising findings, additional stuies incorporating larger randomized controlled trials are necessary to further assess the efficacy and safety of these Ayurvedic approaches for CKD
Keywords: Chronic Kidney Disease (CKD); Glomerular Filtration Rate (GFR); Ayurveda therapies; Panchakarma; Hypertension; Nocturia